2021
DOI: 10.20344/amp.12829
|View full text |Cite|
|
Sign up to set email alerts
|

Abnormal Uterine Bleeding in Adolescents: A Multidisciplinary Approach

Abstract: Abnormal uterine bleeding is the most common complaint that motivates female adolescents to seek medical advice. Abnormal uterine bleeding has a significant impact on quality of life, promoting school absenteeism and limitations in social life. Moreover, episodes can vary from mild to life threatening events if not recognized and treated promptly. Healthcare providers should be able to distinguish between a normal and abnormal menstrual pattern, as this may provide early diagnosis of a potential health concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
8
0
4
Order By: Relevance
“…1 Most cases of anovulatory bleeding can be treated by hormonal and non-hormonal medicines, thus avoiding surgeries. 5 Treating thyroid function has shown to improve the menstrual abnormalities. 6,7 This study aims to find the prevalence of thyroid dysfunction in women of reproductive age with abnormal uterine bleeding in a tertiary hospital of eastern Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…1 Most cases of anovulatory bleeding can be treated by hormonal and non-hormonal medicines, thus avoiding surgeries. 5 Treating thyroid function has shown to improve the menstrual abnormalities. 6,7 This study aims to find the prevalence of thyroid dysfunction in women of reproductive age with abnormal uterine bleeding in a tertiary hospital of eastern Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy menstrual bleeding (HMB), previously known as dysfunctional uterine bleeding, is defined as excessive menstrual bleeding that affects the quality of life physically, socially, emotionally and/or materially. 2 This is not caused by structural abnormalities. 1 Abnormal uterine bleeding occurs in 3-20% of women of reproductive age.…”
Section: Abnormal Uterine Bleedingmentioning
confidence: 98%
“…The incidence in adolescents is higher than in adults (37% versus 10-20%). 2 Heavy menstrual bleeding is the most common symptom. 8 A Swedish study involving 1,000 adolescents found that eISSN (Online): 2598-0580…”
Section: Abnormal Uterine Bleedingmentioning
confidence: 99%
See 2 more Smart Citations